Postpamięć jako marzenie senne – Achtung Zelig! Druga wojna Krzysztofa Gawronkiewicza i Krystiana Rosenberga - Grażyna Gajewska (Images)
Postmemory in the popular culture on the example of the comic novel “Achtung Zelig! The Second War” by Krzysztof Gawronkiewicz & Krystian Rosenberg